1997
DOI: 10.1159/000267990
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Receptors in the Rabbit Iris-Ciliary Body

Abstract: To demonstrate the presence of mineralocorticoid receptors, specifically aldosterone receptors, iris-ciliary body cytosol from New Zealand albino rabbits was incubated with increasing amounts (0.5–20.0 nM) of radiolabeled aldosterone in the presence and absence of a 100-fold excess of aldosterone. A glucocorticoid receptor blocker, RU-28362, was employed when various steroids were allowed to compete with aldosterone for binding sites on the aldosterone receptor. Aldosterone bound to two classes of receptor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The demonstration of mineralocorticoid receptors (MCR) in ocular tissues is supported by a number of different observations, such as specific aldosterone binding in rabbit lens epithelium (Starka, 1977) and in rabbit iris-ciliary body (Schwartz and Wysocki, 1997). In recent studies, we observed the presence of MRC in the eye (Mirshahi et al, 1996(Mirshahi et al, , 1997, and especially in rat Mü ller glial cells (Mirshahi et al, 1997), favoring the possibility that a hormone-regulated ion channel plays a role in ocular physiology.…”
Section: Introductionmentioning
confidence: 85%
“…The demonstration of mineralocorticoid receptors (MCR) in ocular tissues is supported by a number of different observations, such as specific aldosterone binding in rabbit lens epithelium (Starka, 1977) and in rabbit iris-ciliary body (Schwartz and Wysocki, 1997). In recent studies, we observed the presence of MRC in the eye (Mirshahi et al, 1996(Mirshahi et al, , 1997, and especially in rat Mü ller glial cells (Mirshahi et al, 1997), favoring the possibility that a hormone-regulated ion channel plays a role in ocular physiology.…”
Section: Introductionmentioning
confidence: 85%
“…The MR and the 11β-HSD2 are also expressed in the iris and ciliary body [16], [17], which are part of uveal tract, the mid-layer of the eye (Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
“…The notion that ocular sodium transport may be assured by the basolateral Na + -K + -ATPase [1][2][3][4] is not in keeping with the thermodynamic and other properties of the enzyme [5][6][7]. Second, circumstantial evidence suggests that steroid hormones play an important role in ocular sodium ion transport [14][15][16]. Since steroid signaling is the major determinant of ion-water homeostasis in many peripheral tissues and organs [8][9][10], it appeared logical to us that ocular sodium regulation may well follow a similar route.…”
Section: Discussionmentioning
confidence: 99%
“…The participation of mineralocorticoid hormones in ocular ion transport is in fact supported by a number of different observations such as: anticataractogenic influence of mineralocorticoids in experimental animals, opposite effects of cortisol and aldosterone in experimental cataract formation, elevated aldosterone in the lens of hypertensive patients, increased natremia and Na + in the aqueous humor of rabbits treated with aldosterone, development of glaucoma as a result of steroid hormone therapy, specific binding of aldosterone to the mineralocorticoid receptor (MCR) in rabbit lens epithelium [14], rabbit ciliary body [15] and isolated pigmentary epithelial cells [16]. Recently, we provided immunochemical evidence for the presence of the MCR [16,17] and ASSC [18] in a number of rodent ocular tissues in situ.…”
Section: Introductionmentioning
confidence: 92%